The spatial dynamics of land cover change along the Wallacea corridor in the key biodiversity area ‘Buano Island’, Maluku, Indonesia - Bokiraiya Latuamury; Hendrik S E S Aponno; Husain Marasabessy; Miranda H Hadijah; Wilma N Imlabla (Brawijaya University, 2020)
Land cover change is an urgent global issue that needs to be addressed immediately. Its dynamics are of the greatest importance to Key Biodiversity Areas (KBAs) along the Wallacea Corridor, including Buano Island, whose land and sea are rich in biodiversity. KBA Buano Island is home to endemic and endangered birds, such as Moluccan scrubfowl (Eulipoa wallacei) and black-chinned monarch (Monarcha boanensis). Black-chinned monarch only lives on the island (single-site species). Buano waters have an interestingly diverse life, including dugong (Dugong dugon), hawksbill turtle (Eretmochelys imbricata), loggerhead turtle (Caretta caretta), and many species belonging to the dolphin family (Delphinidae) and beaked whale family (Ziphiidae). This study was designed to analyze and map the spatial-temporal patterns of land cover changes on Buano Island. It employed a multi-temporal analysis on Landsat images from 1970, 1980, 1990, 2000, 2010, until now, and a t-test to analyze the results further. The t-test analysis produced t-count ≥ t-table at confidence level (α) of 0.05, indicating significant changes in land cover from 1970, 1980, 1990, 2000, 2010, until 2016. These multitemporal-spatial dynamics were attributable to fluctuation in population growth and open and straightforward access between the island and the capital of the regency. Furthermore, from the aspect of fishery and maritime affairs, Buano Island already had synergistic land area development.